Analisis Promethee II Sebagai Pendukung Keputusan Pemilihan Media Sosial - Saifulloh Saifulloh (Jurnal Teknik Informatika dan Sistem Informasi, 2020)
Nowadays, people cannot get away from social media. Social media is a part of the life of the wider community today, from teenagers to the elderly, many of which use social media to fill their spare time. Trends in the use of social media from various circles of society have many functions, such as news updates, online communication tools, sharing (data, images, and voice) without having to meet face to face. The impact of all social media use, this study aims to select the most popular social media used based on function, interest, or interface. This study uses the Promethee II method as an analysis of social media selection decisions with the results of calculations using Excel 2019. The alternative criteria objects in this study use popular social media such as Instagram, Whatsapp, Facebook, Line, and Telegram. The research method uses the stages of data collection, namely the survey method, distributing questionnaires to respondents to provide responses to the most popular social media assessors.